A Comparative Study Of Plant Interpretation In The Quran Based On Tafsir Al-azhar And Tafsir Al-misbah - Mohammed Akhiruddin Ibrahim; Nur Zaiumi Yasmin Zakaria (Academia Industry Networks, 2024)
Non-Indexed Publication